A reelaboração do político no cinema de Michael Haneke : reenquadramentos do olhar fora de campo - Maya, Bruno da Costa (2019)
The present thesis aims to comprehend the elaboration of the political at Michael Haneke’s cinema though the reframing of the out of field gaze. For this, the films Caché (2005) and The White Ribbon (2009) were analyzed, considering the relations of the visible one of the esthetic regime proposed by Rancière (2014) in the articulation with the political. The intention was to outline how the processes of reframing are fundamental to the change in the logic of the film´s intrigue. In this sense, the thesis will focus in the political aspect of Haneke's cinema as a case of study considering the intention of elaborating the out of field gaze and, as such, with regard to methodology, three categories of analysis were created that are important for the processes of reframing (look at the field, the empty field and the composition of the field). The sequences of the films were selected following the "segmentation" film analysis method proposed by Aumont (2010), and there was a description of the elements of the visual and sound composition (light, sound, scenery), besides the camera movements. In addition to Rancière (2014), the work has as theoretical support the notions of the field out of Burch (1992), Aumont (1993) and Chion (2001), as well as propositions on the image of Deleuze (1990, 1985). Through the investigation of self-reflexive strategies of Caché (2005) and The White Ribbon (2009), it was possible to observe how the elements of the out of the field are constructed by a process of reframing, that is related to the re-elaboration of the political and based on the mystery. This kind of approach, although uses thriller techniques, seeks to escape the logic of the representative regime (Ranciere, 2014).